1995
DOI: 10.1002/1097-0142(19951115)76:10<1747::aid-cncr2820761011>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gallbladder cancer. An international collaborative case–control study

Abstract: Background. Gallbladder cancer has an unusual geographic and demographic distribution, suggesting many possible etiologies. Methods. A case‐control study was undertaken at four hospitals in La Paz, Bolivia, and at one hospital in Mexico City, Mexico. Eighty‐four patients with newly diagnosed, histologically confirmed gallbladder cancer were compared with 126 control subjects without stones and with 264 control subjects with cholelithiasis or choledocholithiasis without cancer. All study subjects underwent abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
143
4
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(158 citation statements)
references
References 13 publications
7
143
4
4
Order By: Relevance
“…A case-control study of gallbladder cancer in Bolivia and Mexico reported that a family history of gallstones was associated with a 3.6-fold risk of gallbladder cancer. 12 The mechanisms are unclear, but it is possible that some yet unidentified susceptibility mechanism may further elevate the risk of biliary tract cancer associated with stones.To investigate the rapid rise in incidence rates of biliary tract cancers in Shanghai, we conducted a large population-based study in Shanghai between 1997 and 2001. In this report, we examined whether a family history of gallstones is an independent risk factor for biliary tract cancer and whether it augments the risk associated with the presence of gallstones.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…A case-control study of gallbladder cancer in Bolivia and Mexico reported that a family history of gallstones was associated with a 3.6-fold risk of gallbladder cancer. 12 The mechanisms are unclear, but it is possible that some yet unidentified susceptibility mechanism may further elevate the risk of biliary tract cancer associated with stones.To investigate the rapid rise in incidence rates of biliary tract cancers in Shanghai, we conducted a large population-based study in Shanghai between 1997 and 2001. In this report, we examined whether a family history of gallstones is an independent risk factor for biliary tract cancer and whether it augments the risk associated with the presence of gallstones.…”
supporting
confidence: 89%
“…A case-control study of gallbladder cancer in Bolivia and Mexico reported that a family history of gallstones was associated with a 3.6-fold risk of gallbladder cancer. 12 The mechanisms are unclear, but it is possible that some yet unidentified susceptibility mechanism may further elevate the risk of biliary tract cancer associated with stones.…”
mentioning
confidence: 99%
“…We identified eight cohort studies Wolk et al, 2001;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Engeland et al, 2005;Kuriyama et al, 2005;Oh et al, 2005) and four case -control studies (Zatonski et al, 1992(Zatonski et al, , 1997Strom et al, 1995;Serra et al, 2002) that reported results on overweight/obesity and risk of gallbladder cancer. One case -control study (Zatonski et al, 1992) was excluded because this study was included in a multicentre case -control study (Zatonski et al, 1997); the multicentre casecontrol study was included in this meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Gallstones are a recognized risk factor for gallbladder cancer. 1,2 The effect of alcohol consumption on gallbladder cancer risk remains controversial throughout the published literature. 3,4 In Sweden, people in different occupations have been shown to have different levels of alcohol intake.…”
Section: Dear Sirmentioning
confidence: 99%